2017
DOI: 10.1299/jamdsm.2017jamdsm0022
|View full text |Cite
|
Sign up to set email alerts
|

Research on layout and operational pose optimization of robot grinding system based on optimal stiffness performance

Abstract: In a robot grinding system, the change of the robot's pose affects the overall stiffness of the whole machining system, which indirectly leads to the irregularity of the grinding surface. For this purpose, we propose a method to enhance the stiffness of the robot. The robot grinding system layout is usually based on the experience of the designer without any quantitative selection criteria. With the introduction of the stiffness performance evaluation index, we decouple the stiffness-couple relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The force vector F corresponding to the upper and lower bounds of η v are: (17) where e vmin and e vmax are the eigenvectors of A v corresponding to λ vmin and λ vmax respectively. Equations (16) and 17give the range of the displacement-force frequency response ratio η v and the amplitudes and phases of the force components for the boundary values of η v . Similar analysis can be carried out on the forced vibration characteristics of the robot under a simple harmonic torque.…”
Section: Frequency Response Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…The force vector F corresponding to the upper and lower bounds of η v are: (17) where e vmin and e vmax are the eigenvectors of A v corresponding to λ vmin and λ vmax respectively. Equations (16) and 17give the range of the displacement-force frequency response ratio η v and the amplitudes and phases of the force components for the boundary values of η v . Similar analysis can be carried out on the forced vibration characteristics of the robot under a simple harmonic torque.…”
Section: Frequency Response Ratiosmentioning
confidence: 99%
“…The process force and torque can excite vibrations into robot structure and lead to much more complicated dynamics than conventional robotic tasks like welding and material handling where only static or low contact forces act on the robot. Since the natural frequencies of an industrial robot strongly depend on its configuration [15] and its stiffness varies significantly in different directions [16,17], the vibration characteristics depend on the robot configuration and the direction of external force. It has been found that structural vibrations of the robot can cause tool misalignment [18], damage the surface quality [19], and reduce the fatigue lives of the tool and the robot [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The positioning of the part to be picked up is an area that affects robotic throughput in an advanced manufacturing environment. With adequate selection and with the simulation-based optimization approach, proper solution that can improve throughput during robotic machining system was developed by considering methods to adjust work pose for easy machining [8] [10].…”
Section: Related Workmentioning
confidence: 99%
“…The configuration of the robot and the cutting force acting on it during machining are dependent upon the pose of the workpiece relative to the robot. It has been found that the natural frequencies of a robot strongly depend on its configuration [34] and that the robot stiffness varies significantly in different directions [35,36] and can be improved by optimizing the robot configuration for a given pick-and-place task [36][37][38], which implies that the vibration characteristics of robotic machining are affected by how the workpiece is placed with respect to the robot. For example, the robot stiffness is considered in Reference [37] for the optimization of the redundant degrees of freedom to minimize the displacement of the cutting tool under static force.…”
Section: Introductionmentioning
confidence: 99%